Perbaikan Manajemen Sistem Gudang di PT. Dewata Cipta Semesta - Tjahjono, Enrico; Felecia, Felecia (Jurnal Titra, 2015)
PT. Dewata Cipta Semesta is a company which focused in sawmills, wood productsÂ produced in the form of cut (sawn timber) for buildingâs materials or furnitureâs raw materials.Â The Warehouse system at the company is still very simple and has many weakness that causeÂ some problems in the company such as the difference between the stock and the physical stock inÂ the warehouse as well as the lenght of the process of unloading. Based on observations and dataÂ analysis on company, there are some problems that result in differences in stock and phusical asÂ well as the duration of the process of unloading are: the arrangement of goods in the warehouseÂ are not grouped in detail, two warehouses head leads, and grading process is carried out whenÂ loading. Warehouse management system improvement is done to minimize the Â differenceÂ between the stock and the physical stock in the warehouse as well as accelerate the process ofÂ unloading the goods. Warehouse management system improvements made are arrange of theÂ raw material warehouse are grouped by type and diameter of the timber , the warehouseÂ material classified by type , grade and size of the timber , making the Standard OperatingÂ Procedure for the warehouse staff. For make the system running properly also proposed toÂ appoint only one head of the warehouse so that there is clarity on the duties and responsibilitiesÂ of the warehouse.Â